The Implementation of Text-Based Approach within the Merdeka Curriculum in Senior High School - Afifah, Afifah; Anisa, Nurul; Rahayu, Siti Aisyah; Hasibuan, Kalayo (Lembaga Riset dan Inovasi Almatani, 2024)
The implementation of a text-based approach in the Merdeka Curriculum at the Senior High School (SMA) level aims to improve students' literacy skills through more holistic and contextual learning methods. This research explores how this approach is implemented, the challenges faced by teachers and students, and the impact it has on learning. The research results show that the text-based approach allows students to understand the subject matter more deeply, improve critical thinking skills, and strengthen communication skills. However, there are obstacles such as lack of resources and adequate teacher training. Recommendations for improvement include providing ongoing teacher training and providing relevant teaching materials.